TO COMPARE INTRAVENOUS FERRIC CARBOXYMALTOSE VERSUS INTRAVENOUS IRON SUCROSE IN POST-PARTUM WOMEN WITH IRON-DEFICIENCY ANEMIA - Karwasara, Vishakha; Prakash, Parul; Datika, Sandeep; Goyal, Priya (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective of this study was to compare intravenous ferric carboxymaltose (FCM) versus intravenous iron sucrose in post-partum women with iron-deficiency anemia (IDA). Methods: This was a hospital-based prospective randomized controlled study, comprising 100 post-natal women with IDA with hemoglobin level <11 g/dL admitted in post-natal ward of the Obstetrics and Gynecology Department in SP Medical College, Bikaner, from June 2021 to May 2022. Results: In age, residence, socioeconomic status, the incidence of IDA in both the groups were comparable and is more among rural areas, low socioeconomic status. Improvement in hemoglobin, serum ferritin, and blood indices in both the iron sucrose and FCM groups, but it was faster and greater with ferric carboxymaltose when compared with iron sucrose. Other advantages are large dose administration at 1 time, therefore, lesser total number of doses required in the FCM group as compared to the IS group. Conclusion: FCM is well tolerated, safer, and effective than iron sucrose in treatment of post-natal IDA.